2014
DOI: 10.3747/co.21.1509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dna-Dependent Protein Kinase Inhibition by NU7026 on dna Repair and Cell Survival in Irradiated Gastric Cancer Cell Line N87

Abstract: Repair of radiation-induced dna double-strand breaks is a key mechanism in cancer cell radioresistance. The synthesized compound NU7026 specifically inhibits dna-dependent protein kinase (dna-pk) within the non-homologous end-joining repair mechanism. Earlier studies demonstrated increased radiosensitivity in dna-pk deficient cells compared with wild-type cells. In chronic leukemia cells, NU7026 appears to enhance the cytotoxic effect of chlorambucil. The radio-modifying effects of NU7026 on cell survival, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that DNA-PK inhibitors can enhance the radiosensitivity of cancer cells (liver cancer HepG2, gastric cancer N87 and leukaemia MOLT-4) by increasing DNA damage leading to G 2 /M phase arrest and induction of apoptosis ( 22 28 ). Similarly, the present results demonstrated that a DNA-PK inhibitor exerted radiosensitization effects on xenograft tumors in vivo and on A549 cells in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that DNA-PK inhibitors can enhance the radiosensitivity of cancer cells (liver cancer HepG2, gastric cancer N87 and leukaemia MOLT-4) by increasing DNA damage leading to G 2 /M phase arrest and induction of apoptosis ( 22 28 ). Similarly, the present results demonstrated that a DNA-PK inhibitor exerted radiosensitization effects on xenograft tumors in vivo and on A549 cells in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that NU7441 did not change the protein expression level of DNA-PKcs, Ku70, and Ku80, but specifically decreased the DNA-PKcs (S2056) protein level. Combined with radiation treatment, NU7441 induced cell-cycle arrest, apoptosis, and enhanced the sensitivity of the cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…Lately, NU7026 has been shown to enhance the cytotoxic effect of irradiation gastric cancer cells. This heightened cytotoxicity was explained by an increase in DSB formation, resulting in G2/M cell arrest and possibly higher levels of apoptosis [ 254 ].…”
Section: The Non-homologous End-joining (Nhej) Proteinsmentioning
confidence: 99%